2003
DOI: 10.1074/jbc.m213070200
|View full text |Cite
|
Sign up to set email alerts
|

TIP120A Associates with Cullins and Modulates Ubiquitin Ligase Activity

Abstract: The cullin-containing ubiquitin-protein isopeptide ligases (E3s) play an important role in regulating the abundance of key proteins involved in cellular processes such as cell cycle and cytokine signaling. They have multisubunit modular structures in which substrate recognition and the catalysis of ubiquitination are carried out by distinct polypeptides. In a search for proteins involved in regulation of cullin-containing E3 ubiquitin ligases we immunopurified CUL4B-containing complex from HeLa cells and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…Nedd8 conjugation reverses p120 CAND1 -mediated inhibition p120 CAND1 was found to selectively interact with unneddylated CUL1 and ROC1/Rbx1 (Liu et al, 2002;Zheng J. et al, 2002;Min et al, 2003;Oshikawa et al, 2003). Moreover, this interaction appeared to cause dissociation of Skp1 from CUL1, hence resulting in inhibition of SCF E3 ligase activity.…”
Section: Nub1-mediated Targeting Of Nedd8 Conjugates To the Proteasomementioning
confidence: 99%
“…Nedd8 conjugation reverses p120 CAND1 -mediated inhibition p120 CAND1 was found to selectively interact with unneddylated CUL1 and ROC1/Rbx1 (Liu et al, 2002;Zheng J. et al, 2002;Min et al, 2003;Oshikawa et al, 2003). Moreover, this interaction appeared to cause dissociation of Skp1 from CUL1, hence resulting in inhibition of SCF E3 ligase activity.…”
Section: Nub1-mediated Targeting Of Nedd8 Conjugates To the Proteasomementioning
confidence: 99%
“…B. Yoon (Yonsei University, Seoul, Korea). The pYR-CD3␦-FLAG construct contains a tetracycline-regulated promoter (18,29). The pYR-CD3␦-FLAG and pTet-off (Clontech) plasmids, which encodes a tetracycline-controlled transactivator, were co-transfected into N2a cells to express CD3␦-FLAG.…”
Section: Methodsmentioning
confidence: 99%
“…A recent crystal structure of the CAND1-Cul1 complex, which showed that Lys 720 in Cul1 is located at the CAND1:Cul1 interface, has provided support for the notion that neddylation of Cul1 and binding of CAND1 are antagonistic (17). However, it is not clear if CAND1 is a global regulator of all cullin-dependent ubiquitin ligase complexes (28,30,45).…”
mentioning
confidence: 99%
“…The second step is the association of a protein known as CAND1 (also termed TIP120A) with the deneddylated cullin protein (17,28,45). CAND1 binds to both N-terminal and C-terminal sequences in Cul1 and blocks binding of the substrate adaptor protein (17,19,28,30,45). Subsequent conjugation of Nedd8 onto the cullin subunit by Ubc12, a Nedd8-specific E2 enzyme (5), is proposed to decrease the affinity of CAND1 for the cullin protein, enabling another substrate adaptor protein (presumably with its bound substrate) to displace CAND1 and initiate another cycle of substrate ubiquitination (5,35).…”
mentioning
confidence: 99%